A cinematographic analysis of English-dubbed Korean films - Miseon Yoon (Humanities & Social Sciences Communications)
Abstract This study investigates dubbing strategies used in Korean-to-English film translations to identify differences between on-screen and off-screen dubbing. The data comprises 12 original and English-dubbed Korean film DVDs released in North America in the 21st century. Using a multimodal corpus ELAN, the film texts are segmented into individual shots, with the dubbed dialogue analyzed based on shot sizes and sound types. Findings reveal that the dubbing of on-screen and off-screen dialogue is independent of each other, indicating the use of distinct approaches in dubbing Korean film dialogue into English. Reduction emerges as the most prevalent translation strategy, regardless of whether the characters are on-screen or off-screen. The study further explores how the linguistic characteristics of the English and Korean contribute to the necessity of reduction in dubbing to match the length of speech.